The Determinants of Funding to Ugandan Nongovernmental Organizations - Fafchamps, Marcel (World Bank, 2012)
Original Ugandan data collected by the authors are used to examine the determinants of funding to local nongovernmental organizations (NGOs). Success in attracting grants from international donors depends mostly on network effects. NGOs that raise in-kind resources locally tend to be young and managed by someone who is simultaneously employed elsewhere. There is some evidence of crowding out: NGOs that receive grant funding are less likely to obtain resources locally, whether in cash or in kind. But this seems to be primarily the result of selection. Once NGO-fixed effects are controlled for, there is no evidence that NGOs receive less revenue from fees and donation after obtaining a grant. These results suggest that donors regard Ugandan NGOs as subcontractors of their development efforts, not as charitable organizations in their own right.